International spillover effects of U.S. tax reforms: Evidence from Germany - Désirée I. Christofzik; Steffen Elstner (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2018)
This paper explores the international transmission of U.S. tax shocks and provides evidence for the German economy. Using structural vector autoregressions, we find that after a U.S. tax cut, German GDP increases moderately. While higher U.S. demand stimulates German exports, a deterioration of price competitiveness lowers this positive growth impulse. The current account increases significantly. Surprisingly, German prices fall as domestic companies reduce unit labor costs. The resulting increase of the real interest rate dampens domestic demand. German tax policy shows an opposite reaction to U.S. tax policy. The latter result, however, is driven by the decade of the 1970s. We find that significant changes in the transmission channels arise by distinguishing between different types of U.S. tax reforms. In particular, in contrast to U.S. personal income tax reforms, changes in the corporate income tax cause a depreciation of the German real effective exchange rate.
Keywords: H20; E32; E62; F44; 330; fiscal policy; tax policy; international spillovers; structural vector autoregressions